Rancang Bangun Sistem Kontrol dan Monitoring Keamanan Sepeda Motor Berbasis IoT dengan Modul GPS Neo-6M dan Sensor Getar SW-420 - Fernando Maesa; Hartono, Hartono (SURYA TEKNIKA, 2025)
Motorcycle security in Indonesia has become an important issue due to the high number of thefts, with 37,684 cases in November 2023, a sharp increase of 165% compared to the previous year. To address this issue, an Internet of Things (IoT)-based security system was developed that integrates the Neo-6M GPS module, SW-420 vibration sensor, and ESP32 WROOM microcontroller. The system enables real-time monitoring of vehicle position, suspicious activity detection, and instant notification delivery through a mobile application. The GPS module results have positioning accuracy with a margin of error of 24.78 meters in open space and 27.94 meters in closed space. While the vibration sensor is able to activate the horn automatically when the position of the vehicle is nudged and moved. The mobile application is designed to make it easier for users to monitor and control vehicles remotely. Based on the survey, 73.4% of users found the app easy to use, while 86.7% found the interface clear and informative. The system is expected to reduce the risk of motorcycle theft through an innovative, practical, and effective IoT solution.